2021
DOI: 10.1136/jitc-2021-003214
|View full text |Cite
|
Sign up to set email alerts
|

Genomic alterations in biliary tract cancer predict prognosis and immunotherapy outcomes

Abstract: BackgroundRecently, immunotherapy with immune checkpoint inhibitors (ICIs) has shown promising efficacy in biliary tract cancer (BTC), which includes gallbladder cancer (GBC) and cholangiocarcinoma (CHOL). Understanding the association between immunotherapy outcomes and the genomic profile of advanced BTC may further improve the clinical benefits from immunotherapy.MethodsGenomic tumor DNA was isolated from 98 Chinese patients with advanced BTC and used for targeted next-generation sequencing of 416 cancer-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 17 publications
2
13
3
Order By: Relevance
“…Inactivation of the APC gene leads to disruption of β-catenin degradation, allowing free β-catenin to accumulate in the cytoplasm and translocate into the nucleus; as it was widely detected in the BTC cells, this was indicated as an early event for the carcinogenesis of BTC ( 42 ). Meanwhile, we found that TP53 and CREBBP alterations were enriched in early-stage BTC patients, which contradicted the result from the previous study ( 43 , 44 ). This difference may be contributed by relatively small sample sizes in their studies and difference in the patient characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…Inactivation of the APC gene leads to disruption of β-catenin degradation, allowing free β-catenin to accumulate in the cytoplasm and translocate into the nucleus; as it was widely detected in the BTC cells, this was indicated as an early event for the carcinogenesis of BTC ( 42 ). Meanwhile, we found that TP53 and CREBBP alterations were enriched in early-stage BTC patients, which contradicted the result from the previous study ( 43 , 44 ). This difference may be contributed by relatively small sample sizes in their studies and difference in the patient characteristics.…”
Section: Discussioncontrasting
confidence: 99%
“…Due to the high level of malignancy and poor prognosis of glioma (Xun et al, 2021), the development of accurate methods is required to predict the associated prognosis and to create effective therapy for patients with glioma. At present, immunotherapy demonstrates high levels of effectiveness in the treatment of malignant tumors (Chen et al, 2021b;Sprooten et al, 2021). Results of previous studies have demonstrated that TIME exhibits a high association with the occurrence and development of several tumor types, and this may act as an important prognostic indicator (Berraondo et al, 2016;Elola et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…TMB serves as a biomarker for prognosis and immunotherapy according to prior study 24 . As a result, the link between TMB and the aforementioned signature was examined in the current investigation.…”
Section: Resultsmentioning
confidence: 99%